2019
DOI: 10.1016/j.eclinm.2019.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Brain-based Classification of Negative Social Bias in Adolescents With Nonsuicidal Self-injury: Findings From Simulated Online Social Interaction

Abstract: Background: Interpersonal stress and perceived rejection have been clinically observed as common triggers of nonsuicidal self-injury (NSSI), with self-injury behavior regulating both affective and social experiences. We investigated whether the subjective interpretation of social interaction in a simulated online environment might be biased in the NSSI group, and the brain mechanisms underlying the experience. Methods: Thirty female adolescent patients with NSSI and thirty female age-matched controls were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Participants with NSSI were recruited from the child and adolescent psychiatric (CAP) clinic in Linköping, Sweden, from June 2016 to March 2018, as part of a study examining neurobiological markers of NSSI in 30 clinical and 30 healthy adolescents which was carried out at the Center for Social and Affective Neuroscience, Linköping University (31). Inclusion criteria for participants were: having engaged in five or more instances of NSSI during the past 6 months, independent of psychiatric diagnosis, and being a female between 15 and 18 years of age.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Participants with NSSI were recruited from the child and adolescent psychiatric (CAP) clinic in Linköping, Sweden, from June 2016 to March 2018, as part of a study examining neurobiological markers of NSSI in 30 clinical and 30 healthy adolescents which was carried out at the Center for Social and Affective Neuroscience, Linköping University (31). Inclusion criteria for participants were: having engaged in five or more instances of NSSI during the past 6 months, independent of psychiatric diagnosis, and being a female between 15 and 18 years of age.…”
Section: Methods Participants and Proceduresmentioning
confidence: 99%
“…Peters, Smart, and Baer (2015) also reported a positive association between rejection sensitivity and self‐harm in a sample of young adults, although, when dysfunctional responses to emotion were adjusted for, the association became non‐significant. Besides, in several recent neuroimaging studies where rejection was experimentally induced, it was found that adolescents with NSSI were high in rejection sensitivity and showed enhanced neural processing of social exclusion, as compared to healthy controls, depression patients, or borderline personality disorder patients (Brown et al ., 2017; Groschwitz, Plener, Groen, Bonenberger, & Abler, 2016; Perini et al ., 2019). Findings from these studies suggest that dispositional rejection sensitivity may also confer risk for NSSI in community adolescents.…”
Section: Rejection Sensitivity and Nssimentioning
confidence: 99%
“…Individuals who engage in NSSI experience greater levels of negative emotions, emotional reactivity, emotion dysregulation (Anderson & Crowther, 2012; S. E. Victor & Klonsky, 2014), and alexithymia, a difficulty in identifying and describing emotions (Lüdtke et al, 2016). Adolescents with NSSI also report that, relative to their peers, they lack social skills (Claes et al, 2010), perceive social situations as more stressful (K. L. Kim et al, 2015), are more sensitive to social rejection (Brown et al, 2017; Perini et al, 2019), and select more maladaptive solutions to social problems (Nock & Mendes, 2008). These emotional and social impairments likely interact to contribute to NSSI engagement.…”
Section: Introductionmentioning
confidence: 99%
“…However, these significant results were eliminated when depressive symptom severity was included as a covariate, leading the authors to conclude that the observed amygdala-frontal circuit disturbances underlie both NSSI and the comorbid depressive symptoms reported by these adolescents - depression is associated with similar alterations in amygdala and prefrontal activation (Arnone et al, 2012; Cullen et al, 2014; Frodl et al, 2009; Phillips et al, 2003), as well as impairments in facial emotion recognition (Demenescu et al, 2010). Studies also associate NSSI with aberrant task-specific neural activation in paradigms involving social evaluation, rejection sensitivity, and social exclusion (Brown et al, 2017; Groschwitz et al, 2016; Malejko et al, 2019; Perini et al, 2019), suggesting NSSI-specific alterations of emotion regulation pathways in social contexts. However, many of these effects were only observed in comparisons to healthy controls, and studies did not control for clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%